TEACHER’S BELIEFS IN EFL WRITING INSTRUCTION: A CASE STUDY OF AN ENGLISH LECTURER AT PADANG STATE POLYTECHNIC - Febriansyah, Gema; Hermawati Syarif; Yetti Zainil (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2023)
Investigating a teacher's beliefs in language teaching is something that needs to be explored. Especially in teaching EFL Writing, examining language teacher beliefs is interested because it can be a benchmark for educators on how EFL Writing teaching happens. In addition, teacher beliefs will also help teachers and learners understand the process of learning. There have been many studies on teacher beliefs towards various English language teaching in Indonesia. However, most of these studies discuss teacher beliefs at the high school level. There is a lack of research on teacher beliefs at the university level. This study focuses on teacher beliefs research on EFL Writing teachers at the university student level. This research used a qualitative method with a case study research design. Observation and in-depth interviews are the instruments of this research. The object of the research is an experienced lecturer at Padang State Polytechnic who has been teaching EFL Writing for approximately 11 years. The results of this study show that the lecturer has several teacher beliefs that he believes to be the basic principles in teaching EFL writing. In addition, in the classroom practice, the lecturer used explicit teaching strategy in teaching EFL Writing. Although there are some difficulties faced by the lecturer in his teaching.